Reflexión y análisis acerca de la remuneración en los contadores públicos de Colombia - Osorio Badel, Manuel Enrique (Universidad Antonio Nariño, 2022)
Public accounting is one of the most important and influential careers in Colombia, its good use facilitates the improvement of the national economy, society and the continuous advancement of companies, the purpose of this article is to create a reflection and recommendations that help public accountants in the development of their activities, since there are no established guidelines that serve as a guide for understanding how and how much is the adequate remuneration for the services provided. Guide the competent entities in such a way with the aim of seeking mechanisms that help achieve equity that benefits the state, companies and professionals, where useful tools are provided for both the employee and the employer, therefore, it was used as primary information collection instruments, a survey aimed at people who work in the accounting sphere, where a general malaise was evidenced regarding the salaries earned, secondary information was collected from bibliographic sources in the different educational portals, they are interpreted and they add the results obtained, ending with the pertinent conclusions.